Structural Investigation into the Causes of Cracks in Building and Solutions: A Case Study (2018)
Cracks are commonly found on and in structures and are usually undesirable features naturally occurring due to age, workmanship and other natural and environmental causes. This study is set to characterize cracks with the principal aim of recommending proper maintenance and efficient repair actions. Crack occurrence in an office building (storey with basement) was investigated as a case study. Reconnaissance survey was carried out to locate and note the tools that would be required for the investigation of the cracks. Visual examination and measurement of cracks to know the cause and type of each crack were performed. Strength test of all the structural members was done using Schmidt hammer to determine the residual strength of the members on which they appear and the results were analyzed. The results of the reconnaissance survey revealed that most of the cracks are located at the left side than at right side elevation of the building. The nature of the cracks showed that 91% are dormant cracks, while 9% are active cracks. Some of the cracks extended to the plastered surface, while the rest extended to the structural elements region. Therefore, the cracks in this building were found to be caused by the drying shrinkage at the wall section, the compressive force from the beams exceeding the ultimate strength of the affected blocks, foundation settlement at the courtyard was also discovered through topographical survey, due to underground erosion of the foundation wall footing. The results of the non-destructive test (NDT) indicated that, the average strength of the structural elements is within acceptable limit.